Green Marketing Orientation Towards Competitive Advantage and Marketing Performance of Non-Food SMEs in Java - Karmel Toryanto, Cheung Jean; Indriani, Farida (International Journal of Scientific Research and Management (IJSRM), 2022)
The importance of sustainability and environmentally friendly activities has led the awareness of green marketing practice. The application of green marketing not only intended for better the environment but also as a competitive advantage towards better marketing performance especially for SMEs which have a very limited capability compared to large companies. This research analyses the green marketing application of non-food SMEs in Java, Indonesia using Green Marketing Orientation (GMO) from Strategic Green Marketing Orientation (SGMO) and Tactical Green Marketing Orientation (TGMO) dimensions. Data was collected from 53 SMEs from various sectors such as home living, clothing, souvenirs and accessories, personal care and beauty, sports and health, automotive, hobbies and collections using 5-point Likert scale questionnaire. The result shows that whiles Strategic Green Marketing Orientation has a positive impact towards competitive advantage and marketing performance, Tactical Green Marketing Orientation does not show the same impact. Findings also reveal the mediating role of competitive advantage for Strategic Marketing Orientation towards SMEs marketing performance.